2013
DOI: 10.1097/ede.0b013e3182949ae7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Residential Exposure to Air Pollution and Lung Cancer Risk

Abstract: Lung cancer incidence in this Canadian study was increased most strongly with NO2 and PM2.5 exposure. Further investigation is needed into possible effects of O3 on development of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
125
4
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 24 publications
5
125
4
6
Order By: Relevance
“…Fixed-site monitor measurements from urban centers were used to conduct a sub-analysis. Results show positive associations of lung cancer incidence with both exposure metrics, with varying degrees of magnitude and significance (Hystad et al 2013). Heck et al examined associations between childhood cancers and traffic-related exposures to PM 2.5 and CO, both in utero, and during the child's first year.…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%
“…Fixed-site monitor measurements from urban centers were used to conduct a sub-analysis. Results show positive associations of lung cancer incidence with both exposure metrics, with varying degrees of magnitude and significance (Hystad et al 2013). Heck et al examined associations between childhood cancers and traffic-related exposures to PM 2.5 and CO, both in utero, and during the child's first year.…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%
“…Currently, using the average concentration of PM2.5/per year reflected environmental risk factors (Pongpiachan et al, 2013). When PM2.5 air concentrations increased each additional 10μg/m3, the incidence of lung cancer would increase 1.29-fold (Hystad et al, 2013). Since 2013, fog haze was frequently in China and PM2.5 average concentration was high over 150μg/ m3, greatly harmed the health of population, in particular caused lung cancer.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Table 1 demonstrates the pronounced impact of smoking and socioeconomic status on lung cancer incidence within the study. Table 3 shows that the estimated effect of PM 2.5 depends considerably on the kind of adjustment chosen by Hystad et al (2013). Interestingly, Table 4 shows effect estimates among never smokers.…”
mentioning
confidence: 99%
“…Interestingly, Table 4 shows effect estimates among never smokers. Although of low precision (only 1,381 never smokers could be studied, among them 120 lung cancer cases), Table 4 in Hystad et al (2013) reported an unexceptional odds ratio of 0.95 for PM 2.5 (per 10 μg/m 3 increase). Similar observations were made in a large pooled case-control study (Olsson et al 2011) on workers exposed to diesel motor emissions (DME).…”
mentioning
confidence: 99%
See 1 more Smart Citation